Electric Power System Planning with Explicit Stochastic Reserves Constraint - Scherer, Charles R.; Joe, Leland (Management Science, 1977)
The problem of optimal planning of an electric power system is formulated as a cost minimizing mixed-integer mathematical program. The model emphasizes system reliability, requiring reserve generating capacity such that a Loss of Load Probability criterion of one day in ten years is met. Integer variables are used in the model to express system reliability explicitly as a constraint on the system model. Results are given for several plant outage rates and demand levels. The results show that the reliability and “rule-of-thumb” approaches to system reserve planning can yield substantially different optimal system costs and configurations.